Preferential Trade Agreements and Productivity: Evidence from Peru - Tello, Mario D. (2023)
This paper analyzes the impact of reducing output tariffs (i.e., domestic tariffs on import of final goods) and input tariffs (i.e., domestic tariffs on imports of intermediate goods) on total factor productivity growth of Peruvian manufacturing firms. Peru’s annual survey of manufacturing data from 2003–2017 is used to explore the reduction of tariffs during three preferential trade agreements: United States, China, and the European Union. Lower output tari?s could decrease productivity by reducing firm’s market share or could increase productivity by inducing tougher import competition, while cheaper imported inputs can raise productivity via learning, variety, and quality effects. The results show that a decrease in output tariffs decreases Peruvian firms’ productivity growth for non-exporters (i.e., domestic firms producing goods that are also imported) while increasing productivity growth for exporters (i.e., domestic firms producing export goods). In contrast, a reduction in input tariffs increases firm productivity for all firms.